2008
DOI: 10.1080/10286020701394332
|View full text |Cite
|
Sign up to set email alerts
|

β-Eudesmol suppresses tumour growth through inhibition of tumour neovascularisation and tumour cell proliferation

Abstract: In the present study, we investigated the potential anti-angiogenic mechanism and anti-tumour activity of beta-eudesmol using in vitro and in vivo experimental models. Proliferation of human umbilical vein endothelial cells (HUVEC) stimulated with vascular endothelial growth factor (VEGF, 30 ng/ml) and basic fibroblast growth factor (bFGF, 30 ng/ml) was significantly inhibited by beta-eudesmol (50-100 microM). Beta-eudesmol (100 microM) also blocked the phosphorylation of cAMP response element binding protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 14 publications
3
39
1
2
Order By: Relevance
“…Therefore, β‐eudesmol may inhibit angiogenesis by suppressing CREB and ERK signalling pathways. In fact, β‐eudesmol significantly inhibited angiogenesis in subcutaneously implanted Matrigel plugs in mice and in adjuvant‐induced granuloma in mice , as well as the growth of H(22) and S(180) mouse tumour in vivo . However, the anti‐angiogenic potential of α‐ or γ‐eudesmol was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, β‐eudesmol may inhibit angiogenesis by suppressing CREB and ERK signalling pathways. In fact, β‐eudesmol significantly inhibited angiogenesis in subcutaneously implanted Matrigel plugs in mice and in adjuvant‐induced granuloma in mice , as well as the growth of H(22) and S(180) mouse tumour in vivo . However, the anti‐angiogenic potential of α‐ or γ‐eudesmol was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ma et al . showed that β‐eudesmol blocked the phosphorylation of cAMP response element binding protein (CREB) induced by VEGF in HUVEC. Therefore, β‐eudesmol may inhibit angiogenesis by suppressing CREB and ERK signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researches on effectiveness of β-eudesmol to blood vessels on the nervous system and also antitumor and anticancer effects have been largely in progress. Apoptotic effect through neovascular control effect of β-eudesmol has been reported (Ikeda and Nagase 2002;Ma et al 2008). And it has been proved that β-eudesmol has apoptotic effect through caspase-3 via caspase-9 caused by cytochrome in HL-60 cells (Hoang et al 2010), c-Jun N-terminal kinase (JNK)-dependent apoptotic effect through mitochondria passage in HL-60 cells (Li et al 2013), and anticancer effects in the experiment of nude mouse to whom it implanted through the method of heterotransplantation of human cholangiocarcinoma (Plengsuriyakarn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Looking at existing studies on β-eudesmol, there have been reports about medical and pharmacologic researches on its anti-inflammation, antimutagenicity, nervous system stabilization, vasodilator, antitumor, and anticancer effects (Li et al 2013;Miyazawa et al 1996;Kimura et al 1991;Chiou and Chang 1992;Satoh et al 1992;Chiou et al 1995;Obara et al 2002;Lim and Kee 2005;Seo et al 2011;Ikeda and Nagase 2002;Ma et al 2008;Plengsuriyakarn et al 2015). However, research on the mechanism of β-eudesmol in human dermal fibroblast has not been reported yet, and also, there have been no researches on β-eudesmol as skin care and cosmetic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…β-eudesmol could significantly promote the gastrointestinal motility in mice (Wang et al, 2002). It has been demonstrated to be an inhibitor for tumor growth (Ma et al, 2008). It might also aid the development of drugs to treat angiogenic diseases (Tsuneki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%